2006
DOI: 10.1149/1.2165743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Filling Performance of a Copper Plating Formula Using a Simple Galvanostat Method

Abstract: This work presents a feasible galvanostat method using a copper working electrode that was individually operated at two different rotation speeds to accurately predict the filling performance of a copper plating formula for microvia filling. This approach is based on the convection-dependent adsorption ͑CDA͒ of additives. Of six copper-plating formulas, formulated to examine the applicability of this method, four were effective for bottom-up filling and two were ineffective. In contrast with the microvia cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
166
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(175 citation statements)
references
References 16 publications
9
166
0
Order By: Relevance
“…In this way, the suppressing effect of the PAG chemistry is effective predominantly at the upper feature side walls and the 3 topmost wafer surface whereas the SPS accelerated copper deposition occurs preferentially at the feature bottom, thus leading to the desired differential electrodeposition. The third constituent of the electroplating bath, the so-called leveler (type-II suppressor) is meant to hinder undesired sustained copper growth (overplating, momentum plating) at the final stage of the deposition process over filled features [20,21]. The leveler action prevents the formation of Cu bumps and their coalescence over dense fields of filled trenches or vias (mounding) which is highly disadvantageous in the subsequent CMP (chemical mechanical polishing) process step [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the suppressing effect of the PAG chemistry is effective predominantly at the upper feature side walls and the 3 topmost wafer surface whereas the SPS accelerated copper deposition occurs preferentially at the feature bottom, thus leading to the desired differential electrodeposition. The third constituent of the electroplating bath, the so-called leveler (type-II suppressor) is meant to hinder undesired sustained copper growth (overplating, momentum plating) at the final stage of the deposition process over filled features [20,21]. The leveler action prevents the formation of Cu bumps and their coalescence over dense fields of filled trenches or vias (mounding) which is highly disadvantageous in the subsequent CMP (chemical mechanical polishing) process step [21].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Dow observed that systems employing these additives, without the use of an accelerator, could be manipulated to suppress deposition on the outer surfaces and near the entrances of holes while allowing the fastest plating to occur in the middles of the holes. Low current densities (1 to 1.6 mA cm −2 ) and long plating times (9 to 12 h) were required.…”
mentioning
confidence: 99%
“…Plugging is then followed by continued filling of the 'blind' holes formed on either side of the plugs. [15][16][17]19 The degree of convection, 15,20 the solution pH, and the specific acid 20 used were found to be important factors in achieving void-free Cu filling of through-holes. These parameters also affect the degree of incorporation of organic species into the Cu deposit and the morphology of the Cu deposit.…”
mentioning
confidence: 99%
“…This phenomenon should stem from a convection-dependent competitive adsorption of additives, whose original occasion was attributed to the potentialdependent adsorption of chloride ions. 13,29,31,34 Figure 7b showed that the cathodic potential was not significantly changed after SPS injection, implying that there was no significant interaction among Polyquaternium-2, chloride ion, and SPS at the low potential. The deposition rate of copper was Cu (II) diffusion-controlled when Polyquaternium-2, chloride ions, and SPS presented in plating solution.…”
Section: Resultsmentioning
confidence: 98%
“…The potential difference at different rotating speed, "©, defined by "© = © 1 (100 rpm) ¹ © 2 (1000 rpm), was used to evaluate the performance of plating. [29][30][31] If the value is positive, it meant that strong convection resulted in less copper deposition; 20 thus, the plating solution might be effective for TH plating, whereas it was ineffective for TH plating if "© was zero or negative. In this study, it was used to characterize the electrochemical behavior of Polyquaternium-2 and it's interaction with other additives in the system.…”
Section: Resultsmentioning
confidence: 99%